Systemic Structure Behind Human Organizations From Civilizations to Individuals - Lin, Yi.; Forrest, Bailey; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
Systemic Structure behind Human Organizations: From Civilizations to Individuals shows how the systemic yoyo model can be successfully employed to study human organizations at three different levels: civilizations, business enterprises, and individuals. This monograph tackles managerial problems from an holistic perspective such as how a business entity grows and dies and how a CEO can manipulate the choices of long- and short-term projects in order to gain more control over the board of directors. By creating a uniform language and logic of reasoning, the book provides examples and convincing results. Additionally the book shows how the same model, thinking logic, and methodology of the systems research can be equally applied to analyze problems and situations considered in natural sciences, social sciences, and humanity areas. Therefore it offers knowledge of a brand new tool to attack organizational problems. By concentrating on difficult, unsettled issues in these varying areas, this monograph thoroughly explains how some laws of nature can be established for the common study of natural and social sciences.
Introduction -- Characteristics of Whole Evolutions -- Several Empirical Justifications -- Elementary Properties of Systemic Yoyos -- The State of a Civilization -- Interactions between Civilizations- Turmoil within a Civilization -- Economic Entities Seen as Spinning Systemic Yoyos -- Economic Eddies and Their Dynamic Equilibrium -- Dynamics between Small and Large Projects -- Nature and Man -- The Four Human Endowments -- Structures of Human Character and Thought -- Happiness, Fear, and Forced Struggle.
Keywords: Economics; Philosophy; Economics/Management Science; Business/Management Science, general; Complex Systems; Philosophy of Man